Tinjauan Yuridis terhadap Perlindungan Pemodal Platform Crowdfunding Kitabisa.Com - Riski Pebru Ariyanti; Aprillaili Aya Tri Kartini; Selvi Wibriana Sari (Faculty of Law Hang Tuah University, 2020)
The advancement of information technology has given rise to innovative ways of obtaining financial support for social purposes as well as business interests. Fundraising is not only done conventionally through, but can also be done online, called crowdfunding. The idea of ​​crowdfunding can be said to be in accordance with the culture of Indonesian society which emphasizes the principle of mutual cooperation, but legal issues that deserve to be studied relate to the protection of investors on crowdfunding platforms. The research used is included in normative juridical research using the statutory approach. The results of the study indicate that the protection of investors against crowdfunding platforms in Indonesia has been regulated in OJK Regulation No. 37 / POJK.04 / 2018 concerning Fund Disbursement Services through Technology-Based Share Offering. OJK Regulation No. 37 / POJK.04 / 2018 is a form of implementation of the supervisory function mandated in Law Number 21 of 2011. Legal protection provided to investors has a preventive nature because it contains substance about the obligations of crowdfunding organizers as well as penalties for mentioning sanctions. if there is a violation. As a new regulation issued at the end of 2018, the need for socialization related to the rules of fund services through the offering of information technology-based shares (equity crowdfunding).